Preservation of Beta Cell Function after Pancreatic Islet Autotransplantation: University of Chicago Experience. Issue 4 (April 2015) - Savari, Omid; Golab, Karolina; Wang, Ling-Jia; Schenck, Lindsay; Grose, Randall; Tibudan, Martin; Ramachandran, Sabarinathan; Chon, W. James; Posner, Mitchell C.; Millis, J. Michael; Matthews, Jeffrey B.; Gelrud, Andres; et al.
The aim of the study was to assess the rate of insulin independence in patients after total pancreatectomy (TP) and islet autotransplantation in our center. TP followed by islet auto-transplantation was performed in 10 patients. Severe unrelenting pain associated with chronic pancreatitis was the major indication for surgery. Islets were isolated using the modified Ricordi method and infused through the portal vein. Exogenous insulin therapy was implemented for at least two months posttransplant to support islet engraftment and was subsequently weaned off, if possible. Median follow-up was 26 months (range, 2 to 60 months). Median islet yield was 158, 860 islet equivalents (IEQ) (range, 40, 203 to 330, 472 IEQ) with an average islet yield of 2, 478 IEQ/g (range, 685 to 6, 002 IEQ/g) of processed pancreas. One patient developed transient partial portal vein thrombosis, which resolved without sequela. Five (50%) patients are currently off insulin with excellent glucose control and HbA1c below 6. Patients who achieved and maintained insulin independence were transplanted with significantly more islets (median, 202, 291 IEQ; range, 145, 000 to 330, 474 IEQ) than patients who required insulin support (64, 348 IEQ; range, 40, 203 to 260, 476 IEQ; P < 0.05). Patient body mass index and time of chronic pancreatitis prior transplant procedure did not correlate with the outcome. The remaining five patients, who require insulin support, had present C-peptide in blood and experience good glucose control without incidence of severe hypoglycemic episodes. Islet autotransplantation efficiently preserved beta cell function in selected patients with chronic pancreatitis and the outcome correlated with transplanted islet mass.